ANALYSIS OF THE IMPLEMENTATION OF FINANCIAL ACCOUNTING STANDARDS OF MICRO, SMALL, AND MEDIUM ENTITIES IN CENTRAL SULAWESI PROVINCE - Muliati Muliati; Arung Gihna Mayapada; Abdul Pattawe (SEIKO : Journal of Management & Business, 2020)
The purpose of this research is to analyze the implementation of Financial Accounting Standards for Micro, Small, and Medium Enterprises (FAS MSMEs) by Micro, Small, and Medium Enterprises (MSMEs) in Central Sulawesi Province. This research is a qualitative descriptive study. The informants included MSMEs supervisors from the the Cooperative, Small, and Medium Enterprises Offices in all regencies/city in Central Sulawesi Province and MSMEs actors in Palu City. The results of this study reveal that MSMEs in Central Sulawesi Province had not implemented accounting and FAS MSMEs properly and correctly. The majority of MSMEs in Central Sulawesi Province only do bookkeeping very simply. This is because MSMEs have insufficient accounting knowledge and skills.